THE IMPACT OF FISCAL DECENTRALIZATION ON EDUCATIONAL PERFORMANCE: A MULTILEVEL ANALYSIS OF THE RELATIONSHIP BETWEEN REGIONAL EXPENDITURE AND STUDENTS' ACADEMIC ACHIEVEMENTS - Herlina; Tri Wahyuni; Hanif Saifullah; Widyatmike Gede Mulawarman; Mukhamad Nurhadi (RADJA PUBLIKA, 2026)
This study analyzes the impact of fiscal decentralization on educational performance at the Senior High School (SMA) and Vocational High School (SMK) levels in Balikpapan City, East Kalimantan Province. Using the framework of human capital theory, this study evaluates the extent to which regional spending allocations are converted into student academic outcomes, as measured by indicators of literacy, numeracy, and graduate absorption. Using a qualitative method with a case study design, data were collected through in-depth interviews with stakeholders at the provincial and educational unit levels, as well as documentation from regional financial reports (APBD) and the 2023-2024 Indonesian Education Report. The results show that although East Kalimantan consistently meets the mandated 20% education budget, the effectiveness of this spending is hampered by administrative complexity following the transfer of authority for managing secondary education from the city government to the provincial government. Multilevel analysis reveals a disconnect between high regional fiscal capacity and resource distribution at the school level, where managerial factors and school autonomy are more dominant determinants in influencing academic competency scores than simply nominal budget volume. This study concludes that strengthening fiscal accountability and policy synchronization between levels of government are essential to optimize education investment in the regions.